Implementasi Evaluasi Partisipatif Dalam Mengetahui Hasil Pembelajaran Senam Lantai Roll Depan pada Siswa SMP Negeri 2 Pebayuran - mohamad yakub; Resty Gustiawati; Muhammad Arif Setiawan (Universitas Singaperbangsa, 2020)
ABSTRACTThe purpose of making this thesis is to know the Participatory Evaluation Implemensi in Knowing the Learning Results of Front Roll Floor Gymnastics in Students of SMP Negeri 2 Pebayuran, which emphasizes Cognitive, Affective, Psychomotor behavior. To answer the formulation of research problems that have been formulated. By researchers using qualitative methods. With obervasi study techniques, interviews, and documentation to obtain the data sought by researchers. By using the interview sheet as a data processing tool that contains questions about what changes are felt in the implementation of participatory evaluation activities in knowing the results of the front roll floor gymnastics learning in SMP Negeri 2 Pebayuran. After the interview data is obtained then an analysis is performed. Qualitative data obtained from the field needs to be recorded carefully and in detail by reducing the data. The purpose of data reduction is to provide a clear picture of the data obtained. After the qualitative data reduction is presented in the form of narrative text.Based on the results of an interview on